THE PEPPER PLANTATION SYSTEM DURING THE EAST INDIA COMPANY ERA IN BENGKULU 1685–1825 - Taufik Hidayat; Febta Pratama; Utomo, Susilo Setyo; Saswal Ukba; Ayu Febriyanti Akbar (Universitas Jember, 2026)
This study aims to analyze the pepper plantation system in Bengkulu during the East India Company (EIC) period from 1685 to 1825, with a particular focus on colonial exploitation mechanisms, labor dynamics, and Bengkulu's integration into global pepper trade networks. The central questions examined include how the EIC constructed its pepper production system, mobilized and exploited labor, implemented colonial policies, and positioned Bengkulu within the global commodity trade. This research employs a historical research methodology encompassing the stages of heuristics, source criticism, interpretation, and historiography, drawing on primary sources from the National Archives of the Republic of Indonesia (ANRI) and Sumatra Factory Records, supplemented by relevant historiographical secondary literature. The study finds that the EIC constructed the pepper plantation system through three primary mechanisms: (1) monopoly agreements with local rulers that obligated each household to cultivate a minimum of 1,000 pepper vines; (2) the use of enslaved African laborers as the operational backbone of the plantation system, with their numbers reaching 1,121 in 1778; and (3) the deployment of British Residents in pepper-producing districts as instruments of colonial control. Bengkulu was integrated into global trade networks through two principal export routes Fort Marlborough–India–London with annual export volumes reaching 453,600–907,200 kg to European markets during the eighteenth century. This study concludes that the EIC's plantation system in Bengkulu constituted a systematic and exploitative form of colonial capitalism, integrating the region into the world economy not for the benefit of its inhabitants, but for the commercial gain of European merchants as evidenced by the recurring resistance of the Bengkulu population throughout the 140 years of EIC occupation.